Relationship between oxidative stress and detrussor overactivity: a case control study - Keske, Murat; Gok, Bahri; Ener, Kemal; Ozcan, Muhammet Fuat; Ozayar, Asim; Okulu, Emrah; Neselioglu, Salim; Cakmak, Serdar; Asil, Erem; Aldemir, Mustafa; Erel, Ozcan (Urology Journal, 2019)
Purpose: We analyzed the role of oxidative stress in detrusor overactivity (DO) by measuring serum total antioxidant capacity (TAC), total oxidant status (TOS), binding capacity of exogenous cobalt to human albumin (IMA), serum advanced oxidation protein products (AOPP), paraoxonase (PON), and arylesterase. Materials and Methods: The study included 38 female patients diagnosed with DO and 29 healthy female subjects forming the control group. Serum total antioxidant capacity (TAC), total oxidant status (TOS), binding capacity of exogenous cobalt to human albumin (IMA), serum advanced oxidation protein products (AOPP), paraoxonase (PON), and arylesterase were analyzed. The results of serum TAC, TOS, IMA, AOPP, PON, and arylesterase of the subjects in both groups were compared. Results: There was no difference between the groups in terms of age. When compared to the control group, serum TAC and IMA levels were statisticaly lower (P < 0,001) and higher (P = 0,003), respectively. However, TOS, AOPP, PON, arylesterase levels were similar in both groups ( p > 0.05 ). Conclusion: There seems to be an association between DO and oxidative damage according to our results, this can be measured by analyzing TAC and IMA in this patient group.